Pretend Play: Children in Control of a Shifting Narrative - Lisa Kervin; Jessica Mantei (MDPI AG, 2022)
Imaginative play is an important part of childhood that provides insight not only into a child's ability to use language, but ultimately into their understandings of the world more broadly. Through play, children control the story as they shape an emerging narrative through words, gestures, movement, and use of play spaces. In this paper we deconstruct a single instance of imaginative play captured in the home corner of a preschool classroom. The unscripted play dialogue creates a shared and compelling narrative evident in the texts the children created and their ongoing and complex interactions. Microanalysis of this narrative provides a novel insight into the play scenarios children create, the resources they select for developing the play, and the ways they communicate. We focus on discourse, subjectivity, and power to analyse the scenario. The cultural and linguistic resources demonstrated by this group of four-year-old children through their play provides insight not only into their understanding and interpretation of activities conducive to the home corner but also into their emerging social identities.